The 4E theory-based performance benchmarking of aged care service provision in community care facilities: a case study of Nanjing, China - Huang, Wei; Hu, Ying; Li, Lingzhi; Wang, Chendi; Liu, Luyao (Frontiers in Public Health, 2025)
The global aging population is growing rapidly, and due to its large population, China is expected to become a ‘super-aged society’ within the next decade. Therefore, ensuring that older people can ‘age in place’ has become a major national priority. Community-care facilities (CCFs) play a key role in this process, but their service performance often faces challenges, with high input costs and limited output benefits. This paper aims to evaluate and improve the social and economic performance of CCFs by proposing a comprehensive framework based on the 4E (Economy, Efficiency, Effectiveness, Equity) theory. Specifically, based on the 4E theory, a literature review and correlation analysis are conducted to select performance indicators. The input–output relationships are then established according to the four dimensions of the 4E theory. These indicators and input–output relationships form the foundation for applying the δ-SBM DEA model, which is used to assess the performance of 75 CCFs in Nanjing. The study finds that the economic performance of CCFs generally lags behind their social performance, with many facilities showing inefficiency in economic indicators, characterized by high operational costs and limited profitability. Projection analysis reveals major issues in low-performing CCFs, including uneven regional distribution of facility performance, poor profitability, a shortage of skilled older people care professionals, and insufficient older people’s participation. Based on these findings, the paper provides specific policy recommendations for government authorities, industry associations, and CCFs, focusing on improving cost-effectiveness, increasing the number of professionals, and enhancing older people’s participation.